Fibroblast subtypes define a metastatic matrisome in breast cancer - Heather M. Brechbuhl; Alexander S. Barrett; Etana Kopin; Jaime C. Hagen; Amy L. Han; Austin E. Gillen; Jessica Finlay-Schultz; Diana M. Cittelly; Philip Owens; Kathryn B. Horwitz; Carol A. Sartorius; Kirk Hansen; et al. (JCI Insight, 2020)
Small primary breast cancers can show surprisingly high potential for metastasis. Clinical decision-making for tumor aggressiveness, including molecular profiling, relies primarily on analysis of the cancer cells. Here we show that this analysis is insufficient — that the stromal microenvironment of the primary tumor plays a key role in tumor cell dissemination and implantation at distant sites. We previously described 2 cancer-associated fibroblasts (CAFs) that either express (CD146+) or lack (CD146–) CD146 (official symbol MCAM, alias MUC18). We now find that when mixed with human breast cancer cells, each fibroblast subtype determines the fate of cancer cells: CD146– fibroblasts promoted increased metastasis compared with CD146+ fibroblasts. Potentially novel quantitative and qualitative proteomic analyses showed that CD146+ CAFs produced an environment rich in basement membrane proteins, while CD146– CAFs exhibited increases in fibronectin 1, lysyl oxidase, and tenascin C, all overexpressed in aggressive disease. We also show clinically that CD146– CAFs predicted for likelihood of lymph node involvement even in small primary tumors (<5 cm). Clearly small tumors enriched for CD146– CAFs require aggressive treatments.